Clinical efficacy of cement application on the basis of mineral trioxide aggregate in case of diagnosed perforative lesions of the teeth roots - Герелюк, Віталій Іванович; Матвійків, Тарас Ігорович; Павелко, Наталія Михайлівна; Павелко, Ігор Йосипович (Actual Dentistry, 2019)
Theme actuality. In case of inadequate treatment of the carious process, there could be significant complications such as pulpitis and apical periodontitis, which lead to the need for root canal treatment or even dental surgical procedures in order to safe the functions of individual teeth. In particular, this relates to perforations of the root canal, where the choosing of adequate root canal filling material and instruments for its obturation and permanent filling are extremely important and emerging. In 1998, the mineral trioxide agregate (MTA) was introduced and proposed for the clinical usage in endodontics and was approved by the FDA as a priority material for the sealing of perforative lesions of the root system of teeth. Nowadays the significant amount of clinical material has been accumulated on the effectiveness of its usagee, which needs to be studied, systematized and analyzed. The purpose of the study: to assess the biocompatibility of the mineral trioxide aggregate filling material during endodontic treatment of perforated root canal lesions. Materials and methods. The criteria for selecting the thematic patients to achieve this goal were clinical cases related to withdrawal of the root canal sealer (MTA)beyond the root system during primary root canal treatment or retreatment. The amount of 13 teeth were studied and treated for the patients aged 35–40 years, including 9 multi rooted and 4 single-rooted teeth of both jaws. Results. On the basis of the obtained data in the treatment by MTA filling material, we might safely summarize about he effectiveness of its usage in clinical situations that were previously considered hopeless. The unique properties of the material allowed to significantly extend the “functioning life” of the treated patients teeth. Conclusion. The Priority of choice and successful clinical application of MTA root canal filling mater in cases of perforative radicular lesions is unquestionably relevant, which is confirmed by favorable clinical outcomes in the examined and treated patients. The authors do not recommend the withdrawal of MTA in periapical tissues, but emphasize its high biocompatibility. The problem of pushing of the MTA in apical periodontal tissues requires further study and discussion. Key words: perforated root canal lesions, MTA dental filling material.